Christ the Lord : the road to Cana : a novel - Rice, Anne, 1941-2021.; Copyright Paperback Collection (Library of Congress) (New York : Anchor Books, 2009)
Anne Rice's second book in her life of Christ series begins during his last winter before his baptism in the Jordan and concludes with the miracle at Cana.--From publisher description.
Previously published by Knopf.
Includes a new introduction and note from the author. -- Cover, p.4.
Keywords: Jesus Christ -- Fiction; Bible. -- History of Biblical events -- Fiction; Religious fiction; Biographical fiction